LABORATORY STAND FOR REMOTE CONTROL REALIZED ON THE MICROCONTROLLER ARDUINO - Federov, Aleksandr; Mangasaryan, Sona; Loginov, Sergei (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
In this article a research principle of remote control of direct current motor with independent excitation is considered. For studying this problem a laboratory stand was made. This project is realized on the microcontroller Arduino. The feature of this stand is the fact that the student needn’t be in a university lab, because the stand is designed for remote control through the Internet. Students can see a scheme of the stand on the monitor of their computers and control it by our program. The advantages of this project are: - The increase security for students, the safety of the laboratory stand. - More accuracy when reading motor parameters. The results of this work can be used not only for studying, but also for practical use at factories in the future.